235k views
4 votes
Solve for all values of p: ​

Solve for all values of p: ​-example-1
User Amin K
by
4.6k points

1 Answer

1 vote

Answer:

p = - 5, p = - 1

Explanation:

Given


(3p)/(p-5) -
(2)/(p+3) =
(p)/(p+3)

Multiply through by the LCM of (p - 5)(p + 3)

3p(p + 3) - 2(p - 5) = p(p - 5) ← distribute parenthesis

3p² + 9p - 2p + 10 = p² - 5p

3p² + 7p + 10 = p² - 5p ( subtract p² - 5p from both sides )

2p² + 12p + 10 = 0 ← divide through by 2

p² + 6p + 5 = 0 ← in standard form

(p + 1)(p + 5) = 0 ← in factored form

Equate each factor to zero and solve for p

p + 1 = 0 ⇒ p = - 1

p + 5 = 0 ⇒ p = - 5

User Dival
by
4.8k points